The use of photodynamic therapy in medical practice - Aebisher, David; Rogóż, Kacper; Myśliwiec, Angelika; Dynarowicz, Klaudia; Wiench, Rafał; Cieślar, Grzegorz; Kawczyk-Krupka, Aleksandra; Bartusik-Aebisher, Dorota (Frontiers in Oncology, 2024)
Photodynamic therapy (PDT) is an approved medical technique for the treatment of certain forms of cancer. Most often, PDT is used as a complement to traditional treatment methods used in today's oncology. In some clinical cases, PDT is used as a replacement for methods such as surgery, chemotherapy or radiotherapy. The critical ingredients of this method are an oxygen, a photosensitizer, the type of which depends on the wavelength used. PDT in the clinic is particularly useful for oncology patients with tumors in hard-to-reach anatomical places and for those whose age and physical condition do not allow the use of another treatment method.